Poverty and its Problems on Islamic View - Tria Manda Sari; Dhea Rahma Novita (Sufiya Research Institute, 2023)
Fast-moving technological developments certainly bring great hope to mankind's welfare. Human efforts have been made to foster a vibrant, dignified civilization. However, in spite of all the efforts made by humans to carry out the mission of civilization, it is undeniable that there are still people who fall into the category of the poor in every country in the world. Islam, as a religion that is believed to change world conditions, certainly has an accurate concept for fighting the poverty rate of the world. The study will therefore reveal some of the studies on poverty as well as how the strategy established by Islam in its mission of poverty reduction. The purpose of this study is a means for anyone to be used as a consideration of decisions.